COMPARATIVE ANALYSIS OF 19TH C DWELLING ARCHITECTURE IN TURKEY AND BULGARIA (Innovation in Woodworking Industry and Engineering design, 2026)
In the past centuries, construction of houses and great public buildings and structures used to be a craft with guild rules and typical dissemination in the region of Balkan Peninsula and different zones in Turkey. We do today admire the majestic residential houses that survived the centuries and could later be restored to be seen in our cities. In the paper, an attempt is made to compare the architectural features of 19th C House in Bulgarian cities, such as Koprivshtitza, Plovdiv, Melnik, etc., to Turkish House, in regions such as Edirne, Bursa and Goynuk. The comparison criteria considered are as follows: Factors for the Development of Architectural Type of Houses (Climatic Considerations, Religion, Livelihood, etc.), Exterior Architectural Image; Interior Organization of Spaces and Furnishings; Building Regulations and Limitations. The goal of the paper is to establish vernacular differences and discover similarities, as an important source of better understanding the spread of architectural types in the past.